MANAGEMENT OF FORMATION OF RESOURCE SUPPORT OF STRATEGIC DEVELOPMENT OF THE ENTERPRISE - AVGUSTYN, RUSLAN; DEMKIV, ІRINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article substantiates the relevance of the development of the principles of management of the formation of resource provision of strategic development of the enterprise in modern conditions of global instability. The main groups of resource provision of the enterprise and the factors of their analysis in the context of the implementation of the model of strategic business development are determined. A formal description of the economic-mathematical model of the optimal distribution of enterprise resources is made. The system of measures of counteraction to obstacles of realization of tasks of model of strategic development of the enterprise caused by insufficiently effective management of resource maintenance is defined. The characteristics of methods of resource provision of the enterprise in the context of its strategic development are given. The resource approach to formation of strategy of development of the enterprise is substantiated. It is stated that in the context of effective planning of strategic business development, resource management for the long term is of key importance and, accordingly, requires careful planning. It is established that the purpose of modeling the strategic development of the enterprise is to increase its market value, which becomes possible due to the formation of a competitive development model. The objective basis for the operation and further development of the entity is capital, which is directly related to the market value of the business, as the capital of the enterprise means the value of resources in tangible, monetary and intangible form, which are invested in the formation of its assets. Accordingly, a significant role in ensuring the strategic development of each enterprise is played by its resource provision. The scientific novelty of the study is to substantiate the system of measures to combat obstacles to the implementation of the strategic development of the enterprise due to insufficient management of resources, as well as the development of methods of resource provision of the enterprise in the context of its strategic development.
Keywords: resource potential; types of resource provision; efficiency of formation and use; management; strategic development of the enterprise